PENGARUH KEPEMIMPINAN ETIS(ETHICAL LEADERSHIP),BUDAYA ORGANISASI, DAN PENGHARGAAN(REWARDS) TERHADAP KETERIKATAN KERJA(WORK ENGAGEMENT)ACCOUNT REPRESENTATIVE (AR) PADA KPP PRATAMA DI LINGKUNGAN KANWIL DJP ‘X’ - Domiyandra, Rimon; Rivai, Hariv Amali (Sekolah Tinggi Ilmu Ekonomi Semarang, 2019)
Employee engagement has become an important issue in human resource management because employee engagement is a key driver in realizing organizational goals. Engaged workers can provide sustainable differentiation for the organization and become a significant competitive advantage. This study aims to examine the influence of ethical leadership, organizational culture, and rewardsto work engagement. The object of this research is the Account Representative (AR) at the tax officeson ‘X’ Regional Tax Offices which amounted to 165 people. This research is a type of quantitative research that is descriptive. From the nature of the problem this research is correlational research. Data processing is done using the SPSS version 16 application. The results showed that ethical leadership, organizational culture, and appreciation had a significant and positive influence on work engagement. From the results of this study it is suggested that organizations give serious attention to efforts to realize the character of ethical storage in their managers, build and implement organizational culture, and develop various forms of appreciation for employee performance, both financial and non-financial awards in order to improve work engagement of employees.